Can Inoculation With the Bacterial Biostimulant Enterobacter sp. Strain 15S Be an Approach for the Smarter P Fertilization of Maize and Cucumber Plants? - Alzate Zuluaga, Mónica Yorlady; Martinez de Oliveira, André Luiz; Valentinuzzi, Fabio; Tiziani, Raphael; Pii, Youry; Mimmo, Tanja; Cesco, Stefano (Frontiers in Plant Science, 2021)
Phosphorus (P) is an essential nutrient for plants. The use of plant growth-promoting bacteria (PGPB) may also improve plant development and enhance nutrient availability, thus providing a promising alternative or supplement to chemical fertilizers. This study aimed to evaluate the effectiveness of Enterobacter sp. strain 15S in improving the growth and P acquisition of maize (monocot) and cucumber (dicot) plants under P-deficient hydroponic conditions, either by itself or by solubilizing an external source of inorganic phosphate (Pi) [Ca3(PO4)2]. The inoculation with Enterobacter 15S elicited different effects on the root architecture and biomass of cucumber and maize depending on the P supply. Under sufficient P, the bacterium induced a positive effect on the whole root system architecture of both plants. However, under P deficiency, the bacterium in combination with Ca3(PO4)2 induced a more remarkable effect on cucumber, while the bacterium alone was better in improving the root system of maize compared to non-inoculated plants. In P-deficient plants, bacterial inoculation also led to a chlorophyll content [soil-plant analysis development (SPAD) index] like that in P-sufficient plants (p < 0.05). Regarding P nutrition, the ionomic analysis indicated that inoculation with Enterobacter 15S increased the allocation of P in roots (+31%) and shoots (+53%) of cucumber plants grown in a P-free nutrient solution (NS) supplemented with the external insoluble phosphate, whereas maize plants inoculated with the bacterium alone showed a higher content of P only in roots (36%) but not in shoots. Furthermore, in P-deficient cucumber plants, all Pi transporter genes (CsPT1.3, CsPT1.4, CsPT1.9, and Cucsa383630.1) were upregulated by the bacterium inoculation, whereas, in P-deficient maize plants, the expression of ZmPT1 and ZmPT5 was downregulated by the bacterial inoculation. Taken together, these results suggest that, in its interaction with P-deficient cucumber plants, Enterobacter strain 15S might have solubilized the Ca3(PO4)2 to help the plants overcome P deficiency, while the association of maize plants with the bacterium might have triggered a different mechanism affecting plant metabolism. Thus, the mechanisms by which Enterobacter 15S improves plant growth and P nutrition are dependent on crop and nutrient status.